2022
DOI: 10.1111/vop.13021
|View full text |Cite
|
Sign up to set email alerts
|

Tear film breakup time and Schirmer tear test in normal dogs: Effects of age, sex, reproductive status, skull type, and nasolacrimal duct patency

Abstract: Objective The present study aimed to determine the effects of age, sex, reproductive status, skull type, and nasolacrimal duct (NLD) patency on tear production and tear film breakup time (TBUT) in normal dogs. Animals studied The ophthalmic data of 82 healthy adult dogs were evaluated in this study. Procedures Age, sex, breed, and reproductive status were recorded. Schirmer tear test (STT) and TBUT were assessed in all dogs, and interferometry was available for the selected dogs. The Jones test was used to eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 31 publications
4
18
0
Order By: Relevance
“…A single study has previously evaluated TFBUT in brachycephalic breeds compared to non‐brachycephalic breeds, demonstrating a significantly more rapid TFBUT of 1.3 s in normal brachycephalic dogs compared to normal non‐brachycephalic dogs 14 . The current study found a TFBUT difference of 4.3 s between the treated group and the control group, and so, the relative increased presence of brachycephalic animals in the treatment group was unlikely to be significant enough alone to cause this vastly larger discrepancy in TFBUT values observed in the treated group.…”
Section: Discussionmentioning
confidence: 99%
“…A single study has previously evaluated TFBUT in brachycephalic breeds compared to non‐brachycephalic breeds, demonstrating a significantly more rapid TFBUT of 1.3 s in normal brachycephalic dogs compared to normal non‐brachycephalic dogs 14 . The current study found a TFBUT difference of 4.3 s between the treated group and the control group, and so, the relative increased presence of brachycephalic animals in the treatment group was unlikely to be significant enough alone to cause this vastly larger discrepancy in TFBUT values observed in the treated group.…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians can evaluate tear film stability using the tear film breakup time (TFBUT), a diagnostic test that provides an indirect measure of pre‐ocular mucins 77 and that correlates well with lipid layer thickness 78 . TFBUT is generally reduced in brachycephalic dogs 23,61,79,80 . A recent study of 82 healthy adult dogs showed that TFBUT was significantly lower in brachycephalic compared with non‐brachycephalic dogs 61 .…”
Section: Ocular Surface Disease In Brachycephalic Dogsmentioning
confidence: 99%
“…A highly cited publication from 2006 showed that tear production decreases with age in the normal dog, 60 but this information is not supported by several other studies. [61][62][63] In fact, it is possible that aqueous tear secretion remains normal with advancing age as a compensatory mechanism to developing qualitative tear film deficiency. 61…”
Section: The Aging Ocular Surface Of Brachycephalic Dogsmentioning
confidence: 99%
See 1 more Smart Citation
“…TFBUT is negatively correlated with age, 23 and it is shorter in brachycephalic compared to non-brachycephalic dogs. 83 Additionally, average TFBUT appears to vary greatly among canine breeds: 5.3 s (Shih Tzus), 23 8-9 s (Pugs), 13 8.45-10.77 s (variety of brachycephalic breeds), 84 13.9 s (West Highland White Terrier), 12 and 19.38-24.0 s (Beagles). 29,64,85…”
Section: Strip Meniscometry Tube (Smt)mentioning
confidence: 99%